2016
DOI: 10.1002/ejoc.201600778
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Phase Synthesis of the Macrocyclic Core of Teixobactin

Abstract: Towards the total chemical synthesis of the exceptionally potent antibiotic teixobactin, we synthesized the macrocyclic core of a natural product by using a solution‐phase approach. The gramscale synthesis of l‐allo‐enduracididine and Shiina macrolactonization are highlights of the present disclosure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Two reports of the total synthesis of teixobactin have been published, 4,5 as well as a third describing the synthesis of the cyclic depsipeptide ring. 6 A 10-step synthesis of allo -enduracididine suitable for preparing gram-quantities has also been reported. 7 Several research groups have reported structure-activity relationship studies of Arg 10 -teixobactin (Fig.…”
mentioning
confidence: 99%
“…Two reports of the total synthesis of teixobactin have been published, 4,5 as well as a third describing the synthesis of the cyclic depsipeptide ring. 6 A 10-step synthesis of allo -enduracididine suitable for preparing gram-quantities has also been reported. 7 Several research groups have reported structure-activity relationship studies of Arg 10 -teixobactin (Fig.…”
mentioning
confidence: 99%
“…The macrocycle of teixobactin contains 13 backbone atoms; therefore, the point of cyclisation is critical because an efficient reaction is dependent on the conformation that the peptide adopts. A solution‐phase synthesis of the macrocyclic core was previously achieved with yields in the order of 50% to 55% . For our strategy (Scheme A), we assembled the linear precursor such that the more flexible side‐chain of D‐Thr 8 was located in the middle of the linear peptide.…”
Section: Resultsmentioning
confidence: 99%
“…A solutionphase synthesis of the macrocyclic core was previously achieved with yields in the order of 50% to 55%. 24 For our strategy (Scheme 1A), we assembled the linear precursor such that the more flexible side-chain EDC.HCl was used because it is inexpensive and can be readily extracted from the reaction mixture with aqueous washes prior to Boc deprotection. Each synthetic step was characterised via LC-MS (refer to Figure 2A for details).…”
Section: Resultsmentioning
confidence: 99%
“…By using as imilar strategy,R eddy and co-workers achieved gram-scales ynthesis of the l-allo-End building block, allowingf or the synthesis of the teixobactin macrocyclic core. [26] In this synthetic route, 8 was furtherd erivatized by CbzCl to give fully protected l-allo-End. However, the Cbzp rotecting group wasu nable to be completely removed from the final macrocyclized product, and this is possibly due to the intramolecularh ydrogen bonding between nitrogen atom and the carboxylic acid group on the enduracididine ring.…”
Section: Chemical Synthesis Of L-allo-endmentioning
confidence: 99%